MicroRNA-375 regulates glucose metabolism-related signaling for insulin secretion. Issue 1 (January 2020) - Dumortier, Olivier; Fabris, Gaia; Pisani, Didier F; Casamento, Virginie; Gautier, Nadine; Hinault, Charlotte; Lebrun, Patricia; Duranton, Christophe; Tauc, Michel; Dalle, Stéphane; Kerr-Conte, Julie; Pattou, François; et al.
Abstract : Enhanced beta cell glycolytic and oxidative metabolism are necessary for glucose-induced insulin secretion. While several microRNAs modulate beta cell homeostasis, miR-375 stands out as it is highly expressed in beta cells where it regulates beta cell function, proliferation and differentiation. As glucose metabolism is central in all aspects of beta cell functioning, we investigated the role of miR-375 in this process using human and rat islets; the latter being an appropriate model for in-depth investigation. We used forced expression and repression of mR-375 in rat and human primary islet cells followed by analysis of insulin secretion and metabolism. Additionally, miR-375 expression and glucose-induced insulin secretion were compared in islets from rats at different developmental ages. We found that overexpressing of miR-375 in rat and human islet cells blunted insulin secretion in response to glucose but not to α-ketoisocaproate or KCl. Further, miR-375 reduced O2 consumption related to glycolysis and pyruvate metabolism, but not in response to α-ketoisocaproate. Concomitantly, lactate production was augmented suggesting that glucose-derived pyruvate is shifted away from mitochondria. Forced miR-375 expression in rat or human islets increased mRNA levels of pyruvate dehydrogenase kinase-4, but decreased those of pyruvate carboxylase and malate dehydrogenase1. Finally, reduced miR-375 expression was associated with maturation of fetal rat beta cells and acquisition of glucose-induced insulin secretion function. Altogether our findings identify miR-375 as an efficacious regulator of beta cell glucose metabolism and of insulin secretion, and could be determinant to functional beta cell developmental maturation.